2020
DOI: 10.1037/cou0000413
|View full text |Cite
|
Sign up to set email alerts
|

Career-related parental behaviors, adolescents’ consideration of future consequences, and career adaptability: A three-wave longitudinal study.

Abstract: Career adaptability is a critical psychological resource for adolescents during their transition from secondary to postsecondary education. Based on prospective data from 451 Chinese adolescents (M ϭ 16.87, SD ϭ 0.63; 46.3% female), this study examined the mediating role of adolescents' consideration of future consequences (CFCS) in the association between career-related parental behaviors and adolescents' career adaptability. Results demonstrated that career-related parental support at Wave 1 was associated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…The identified mediating role of teacher–student relationship quality in the association between family SES and adolescents’ career ambivalence is consistent with propositions from the general Family Investment Model (FIM; Conger & Donnellan, 2007), the Family Stress Model (FSM; Masarik & Conger, 2017), and the specific Lent et al’s (2000) SSCT. Family economic status is associated with the amount and quality of resources that parents are able to invest in either parenting processes/parent–child relationship or learning materials to their children (Liang et al, 2020). Adolescents tend to perceive a sense of uncertainty and threat in terms of their future careers (e.g., competing for limited college entrance and job vacancies) and thus they have to learn to allocate their resources to meet their respective needs (Melloy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified mediating role of teacher–student relationship quality in the association between family SES and adolescents’ career ambivalence is consistent with propositions from the general Family Investment Model (FIM; Conger & Donnellan, 2007), the Family Stress Model (FSM; Masarik & Conger, 2017), and the specific Lent et al’s (2000) SSCT. Family economic status is associated with the amount and quality of resources that parents are able to invest in either parenting processes/parent–child relationship or learning materials to their children (Liang et al, 2020). Adolescents tend to perceive a sense of uncertainty and threat in terms of their future careers (e.g., competing for limited college entrance and job vacancies) and thus they have to learn to allocate their resources to meet their respective needs (Melloy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to rate the items on a 5-point scale from 1 (“ Definitely not like me ”) to 5 (“ Very much like me ”). The scale had good reliability and validity in Chinese samples (Liang et al, 2020). In the current study, factor loadings of the indicators ( rs = .62 to .86) were between .77 to .96 at W1 and W3.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding CA, past studies have focused on general company employees ( AlKhemeiri et al, 2020 ; Omar and Tajudeen, 2020 ; Wang et al, 2021 ), student veterans or veterans ( Ghosh and Fouad, 2018 ; Ghosh et al, 2019 ; Becker et al, 2022 ), college students ( Gregor et al, 2021 ; Hu et al, 2021 ; Kim and Smith, 2021 ), high school students ( Dostanić et al, 2021 ), adolescent groups ( Liang et al, 2020 ; Bacanli and Sarsikoğlu, 2021 ), and working women ( Takawira, 2020 ), and have revealed that the target population is very diverse and represents the importance of research on CA.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, most of these studies focused on students’ parental behaviors, expectations of students, and caring support ( Liang et al, 2020 ; Parola and Marcionetti, 2021 ; Nikander et al, 2022 ). External variables, or students’ internal personality traits and active personality ( Bacanli and Sarsikoğlu, 2021 ; Hu et al, 2021 ; Chang and Liu, 2022 ) have been less frequently explored in terms of MT, SE, and other intrinsic subjective drivers that are at the core of a person’s being from a self-deterministic perspective.…”
Section: Introductionmentioning
confidence: 99%